Early detection of glaucoma by means of a novel 3D computer-automated visual field test. Issue 10 (15th May 2007) - Nazemi, Paul P; Fink, Wolfgang; Sadun, Alfredo A; Francis, Brian; Minckler, Donald
Abstract : Purpose: A recently devised 3D computer-automated threshold Amsler grid test was used to identify early and distinctive defects in people with suspected glaucoma. Further, the location, shape and depth of these field defects were characterised. Finally, the visual fields were compared with those obtained by standard automated perimetry. Patients and methods: Glaucoma suspects were defined as those having elevated intraocular pressure (>21 mm Hg) or cup-to-disc ratio of >0.5. 33 patients and 66 eyes with risk factors for glaucoma were examined. 15 patients and 23 eyes with no risk factors were tested as controls. The recently developed 3D computer-automated threshold Amsler grid test was used. The test exhibits a grid on a computer screen at a preselected greyscale and angular resolution, and allows patients to trace those areas on the grid that are missing in their visual field using a touch screen. The 5-minute test required that the patients repeatedly outline scotomas on a touch screen with varied displays of contrast while maintaining their gaze on a central fixation marker. A 3D depiction of the visual field defects was then obtained that was further characterised by the location, shape and depth of the scotomas. The exam was repeated three times per eye. The results were compared to Humphrey visual field tests (ie, achromatic standard or SITA standard 30-2 or 24-2). Results: In this pilot study 79% of the eyes tested in the glaucoma-suspect group repeatedly demonstrated visual field loss with the 3D perimetry. The 3D depictions of visual field loss associated with these risk factors were all characteristic of or compatible with glaucoma. 71% of the eyes demonstrated arcuate defects or a nasal step. Constricted visual fields were shown in 29% of the eyes. No visual field changes were detected in the control group. Conclusions: The 3D computer-automated threshold Amsler grid test may demonstrate visual field abnormalities characteristic of glaucoma in glaucoma suspects with normal achromatic Humphrey visual field testing. This test may be used as a screening tool for the early detection of glaucoma.